The Effect of Progressive Muscle Relaxation on Pain Reduction And Sleep Quality in Dyspepsia Functional Patients in the Inpatient Room of Muhammadiyah RSU Lumajang - Damara, Doni; Salam, Ainul Yaqin; Kusyairi, Achmad (Research of Service Administration Health and Sains Healthys, 2024)
Often, these health problems are linked to unhealthy lifestyles. However, the consumption of food and beverages, as well as side effects from medications, also contribute to functional dyspepsia. One of the symptoms that appears is heartburn. Inadequate pain management and care can be unbearable for patients with functional dyspepsia, interfering with daily activities and affecting sleep quality at night. The research design employed a pre-experimental approach using a cross-sectional design. The population in this study consisted of inpatients with an average monthly visit during January-April 2024, with 74 functional dyspepsia patients. The sampling technique used Accidental Sampling over 14 days, resulting in a sample of 27 respondents. To determine the relationship between the two variables, the Wilcoxon Signed Rank Test was used with a significance level of 0.05. The research results showed that almost all respondents experienced mild pain (25 respondents, 92.6%) and almost all respondents experienced an improvement in sleep quality (26 respondents, 96.3%) after progressive muscle relaxation. After conducting the Wilcoxon Signed Rank Test, the results showed a Sig. value (2-tailed) of 0.000 < 0.05, so H0 was rejected and H1 was accepted, meaning that there is a significant correlation between progressive muscle relaxation and the reduction of pain and improvement in sleep quality in patients with functional dyspepsia in the inpatient ward of Muhammadiyah General Hospital Lumajang. It is hoped Muhammadiyah General Hospital Lumajang can implement progressive muscle relaxation as a non-pharmacological therapy for patients with pain and decreased sleep quality due to functional dyspepsia or other diseases with similar symptoms.